IMPACT OF WATER OVEREXPLOITATION ON HIGHLAND LAKES OF EASTERN ETHIOPIA - Alemayehu T.; Furi W.; Legesse D. (My University, 2007)
The eastern Ethiopian highland is endowed with large potential of water resources in terms of rainfall, groundwater and surface water. Yet, due to overpumping of lake water and groundwater and environmental degradation, Lakes Haromaya and Adele have completely dried up. The environmental degradation, due to deforestation and clearing of land for farming, has increased the rate of siltation in the lakes that dramatically decreases the lakes’ volume and surface albedo, which increased the rate of evaporation. The impact of these factors is aggravated due to decreasing net recharge to the lake and the alluvial aquifer. Over the last 35 years, pumping of lake water for irrigation, mainly for subsistence farming, domestic and industrial use shows an increasing trend. Hence, the available water for drinking and industrial purposes decreased drastically. In this research, classical Penman aerodynamic combined energy budget, Penman nomogram methods, conventional soil moisture water balance method and Penman–Monteith model were adopted to estimate free evaporation, actual and potential evapotranspirations. The results indicate that evaporation is the dominant factor for the loss of water and water abstraction is 316% higher than the effective precipitation, which is 110 mm/year. Therefore, overexploitation of the available resources has played an aggravating role for the loss of the lakes in the area. The main cause for such resource depletion is the lack of integrated water resources management strategies. The current water shortage in the area has mainly affected urban residents of Harar, Awoday and Alemaya towns and the surrounding villages, which depend heavily on the two lakes. To alleviate the current crises interbasin water transfer and rainwater harvesting would be possible alternatives besides ameliorating environmental situation of the basin.
Keywords: GROUNDWATER; EVAPORATION; SURFACE WATER; WATER RESOURCES